Fiscal adjustment, conditionality and politics in IMF programs - Ladeira, Carlos Eduardo de Almeida (2015)
A common feature in programs of the International Monetary Fund (IMF) is the use of conditionalities, macroeconomic and structural measures that a requesting country should adopt to obtain an assistance package. The objective of this work is to conduct an empirical analysis of the economic and political determinants of such conditionalities. In particular, our main contribution consists in the development of a new measure of conditionality, fiscal adjustment, and its comparison with the most used in the literature, the number of conditions. We choose fiscal adjustment because it is an adequate proxy for program austerity, since its implementation carries economic and political costs. In the empirical exercise, we use data from 184 programs in the period of 1999 and 2012, and estimate how our two measures of conditionalities respond to the economic and political factors. Our results suggest that they are quite different. The main determinant of the number of conditions is the political proximity of the borrowing country to the Fund’s major shareholders, the members of G5. On the other hand, the main determinant of fiscal adjustment is the size of the government fiscal deficit. Finally, we did not find correlation between the size of fiscal adjustment and the number of conditions. These results suggest that the analysis of the content of IMF programs should take into account the different measures of agreed conditionality.